HLA and duodenal ulcer. Issue 9 (September 1979) - Ellis, A; Woodrow, J C
Abstract : One hundred and one white patients, consisting of 78 men and 23 women, with duodenal ulcer were HLA typed. An association was found between duodenal ulcer and HLA-B12.